A bi-directional coupling of 2D shallow water and 3D Reynolds-averaged Navier–Stokes models. Issue 6 (2nd November 2018) - Mintgen, Florian; Manhart, Michael
ABSTRACT: A parallelized numerical coupling between shallow water equations and Reynolds-averaged Navier–Stokes equations is presented. The coupling is implemented via a bi-directional exchange of flow variables at the interfaces between shallow water and Reynolds equations, thus allowing for the computation of unsteady phenomena such as flood waves. Several test cases are conducted, in which coupled simulations are compared to both shallow water simulations and Reynolds-averaged Navier–Stokes simulations. It is shown that shallow water waves traverse the interface between both regions without significant distortion. For a complex scenario of a flood wave approaching an obstacle, it is demonstrated that the method is computationally efficient and that it is stable and accurate even in cases where basic assumptions of the shallow water equations are violated.